SphGLLTools: A toolbox for visualization of large seismic model files based on 3D spectral-element meshes. (February 2022) - Ciardelli, Caio; Bozdağ, Ebru; Peter, Daniel; van der Lee, Suzan
Abstract: Adjoint tomography, a full-waveform inversion technique based on 3D wave simulations, has become a commonly used tool in passive-source seismology, drawing on advances in computational power and numerical methods. From global to reservoir scales, seismic models can iteratively be updated in adjoint inversions by extracting information from full seismic waveforms. Seismic models are typically constructed on the numerical mesh used for wave simulations. Thus the size of model files depends on the minimum resolvable period achieved in simulations controlled by the numerical mesh (the higher the mesh resolution, the larger the model and mesh files). This is specifically a concern for recent global-scale adjoint tomographic models where the size and format of numerical meshes pose challenges for model visualization, analysis, interpretation, and sharing model files. Here, we present SphGLLTools, an open-source toolbox that intends to diminish these challenges by expanding global adjoint models onto spherical harmonic functions, which are widely used in global seismology. Our tools are initially designed for spectral-element meshes used in recent global adjoint tomography studies. SphGLLTools facilitate many commonplace tasks for model visualization and analysis, including spherical harmonic expansion of models sampled on spectral-element meshes together with associated tools for easy sharing, visualization, and interpretation of large-scale seismic model files. All the developed routines are accompanied by user instructions and are available through GitHub . For transparency, reproducibility, and educational purposes, we also include Colab notebooks, which provide an intuitive and comprehensive review of the principles and methods for spectral-element meshes, spherical harmonic expansion, and other model analysis tools. Highlights: An open-source toolbox for efficient visualization and sharing global adjoint models. A complete and detailed manual, including examples. Colab notebooks for transparency, reproducibility, and educational purposes.